Study on the simulation of bridge deformation in a mining subsidence area - Chi Zhang; Kan Wu; Shengxiang Huang; Lingai Li; Xiaokang Rao (Scientific Reports)
Abstract Bridges in mining areas deform primarily because of surface subsidence caused by underground mining. Analysis of these deformations should consider the synergistic effects between the foundation soil and the bridge superstructure. The geology of mining areas, which is inherently complex, significantly effects the selection of soil mechanics parameters, potentially leading to errors in model calculations. This study focuses on the bridge in the Fengfeng mining area of Handan, Hebei, and uses the probabilistic integral method to predict subsidence at the bottom section below the surface over a specified period. A finite element model of the bridge and foundation soil is constructed, utilising these predicted subsidence contour lines as boundary conditions for simulating the surrounding surface subsidence. Additionally, monitoring data of surface and bridge subsidence from the same period are collected to validate the simulation accuracy, analyse error types and causes, and propose model improvements. After the feasibility of the improvement schemes is validated, the revised model is employed to predict the bridge failure trend. The model parameters can be adjusted based on surface subsidence monitoring data, and by integrating these adjustments with the predicted subsidence results at the bottom section during various mining stages, the bridge failure trend can be accurately predicted.